TAXIATOSh SOHILBOʻYI VA SUV OʻSIMLIKLARINI TASNIFLAShNING ASOSIY TUShUNChALARI - Rustamova, S.R.; Utemuratova, G.N.; Otenova, F.T. (SCIENCE and SOCIETY, 2025)
The article discusses the basic concepts of classification of coastal and aquatic vegetation. The study analyzes the environmental significance of these plants, their habitat conditions and classification criteria. Methods of geobotanical and ecological description were used as a methodological approach, and factors influencing aquatic ecosystems were studied. The results indicate that riparian and aquatic plants in Tahiyatash play an important role in maintaining the ecological balance. The study findings provide recommendations for the protection of these plants and directions for further research.
Keywords: coastal plants; aquatic plants; classification; ecological factors; aquatic ecosystems